2009
DOI: 10.1177/1091581809337738
|View full text |Cite
|
Sign up to set email alerts
|

Final Report of the Safety Assessment of Hyaluronic Acid, Potassium Hyaluronate, and Sodium Hyaluronate

Abstract: Hyaluronic acid, sodium hyaluronate, and potassium hyaluronate function in cosmetics as skin conditioning agents at concentrations up to 2%. Hyaluronic acid, primarily obtained from bacterial fermentation and rooster combs, does penetrate to the dermis. Hyaluronic acid was not toxic in a wide range of acute animal toxicity studies, over several species and with different exposure routes. Hyaluronic acid was not immunogenic, nor was it a sensitizer in animal studies. Hyaluronic acid was not a reproductive or de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
0
15

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(81 citation statements)
references
References 211 publications
(234 reference statements)
0
66
0
15
Order By: Relevance
“…HA, a naturally derived polysaccharide, has demonstrated excellent biocompatibility and low cytotoxicity in various studies and applications [15]. One proposed method of HA application is either as a spray coating [16] or as an irrigation solution [17].…”
Section: Introductionmentioning
confidence: 99%
“…HA, a naturally derived polysaccharide, has demonstrated excellent biocompatibility and low cytotoxicity in various studies and applications [15]. One proposed method of HA application is either as a spray coating [16] or as an irrigation solution [17].…”
Section: Introductionmentioning
confidence: 99%
“…HA is known as a biocompatible polymer and studies have shown that it is safe for concentrations up to 1-2% (W/V) [17,18]. Comparing the results obtained for the HA and HASSNH 2 polymers, no statistical differences were observed in all four tested situations.…”
Section: Polymer Modification Did Not Affect Cytotoxicitymentioning
confidence: 78%
“…Les réactions inflammatoires locales immé-diates et non allergiques (érythème, tuméfaction) sont fré-quentes (8 % des cas) : elles disparaissent sans traitement [2]. Les réactions d'hypersensibilité aiguës et graves (anaphylaxie, urticaire, angioedème) sont rares (0,6 % des cas) [6,16,17].…”
Section: Discussionunclassified